Top–down and bottom–up control of visual selection - Theeuwes, Jan (Acta psychologica, 2010)
The present paper argues for the notion that when attention is spread across the visual field in the first sweep of information through the brain visual selection is completely stimulus-driven. Only later in time, through recurrent feedback processing, volitional control based on expectancy and goal set will bias visual selection in a top–down manner. Here we review behavioral evidence as well as evidence from ERP, fMRI, TMS and single cell recording consistent with stimulus-driven selection. Alternative viewpoints that assume a large role for top–down processing are discussed. It is argued that in most cases evidence supporting top–down control on visual selection in fact demonstrates top–down control on processes occurring later in time, following initial selection. We conclude that top–down knowledge regarding non-spatial features of the objects cannot alter the initial selection priority. Only by adjusting the size of the attentional window, the initial sweep of information through the brain may be altered in a top–down way.